The Analysis Of Complete Basic Immunization Low Coverage During Covid-19 Pandemic At Community Health Center Pekanbaru - SAHIRA, NUZUL RIFQA (Jurnal Vokasi Indonesia, 2026)
Complete Basic Immunization (IDL) is the giving of early immunization to infants before their age below one year old consisting of Hepatitis B, BCG, DPT-HB-Hib, Polio (IPV and OPV) and measles. Giving Immunization to children can prevent the occurrence of disease transmission (PD3I). The lowest IDL coverage in Pekanbaru Community Health Center during the Covid-19 pandemic experienced a significant decrease of 58.1%. The study objective was to analyze low IDL coverage in infants during the Covid-19 pandemic. The method was qualitative with phenomenology design. The study informant was 11 people. Data collection was conducted through in-deep interview, observation and document review. Data analysis was by the content analysis method. The results showed that the low coverage of IDL caused by Human Resources (SDM) for immunization was transferred to the handling of Covid-19, Posyandu was not implemented during the Covid-19 pandemic, the implementation of Immunization in Health Centers was not carried out every month, immunization services were transferred to Independent Practice Midwives (BPM), no report on basic immunization data report from BPM, parents felt safe if immunization in health services that were not crowded, immunization funding in health centers is by the government and monitoring of IDL coverage has been conducted. It can be concluded that the Covid-19 outbreak greatly affects the low coverage of Complete Basic Immunization. It is recommended that the health center advocate to the Health Office for increasing the number health workers, giving training for caders, increase community empowerment through print media such as posters, cooperating with midwife and hospital practices and then creating Whatsapp groups with mothers who have babies to provide information and share about immunization